2020
DOI: 10.3390/insects11090635
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Mating Disruption Program for a Mealybug, Planococcus ficus, in Vineyards

Abstract: The vine mealybug (VMB), Planococcus ficus (Hemiptera: Pseudococcidae), is a key insect pest of vineyards, and improvements in sustainable control of this pest are needed to meet increasing consumer demand for organically farmed products. One promising option is mating disruption. In a series of experiments conducted from 2004 to 2007, we tested the effects of mating disruption on trap captures of Pl. ficus males in pheromone-baited traps, on Pl. ficus numbers and age structure on vines, and on damage to grape… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
21
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 58 publications
1
21
0
Order By: Relevance
“…Previously, studies showing the usefulness of this technique as a control tool for a mealybug species have been carried out only for Pl. ficus in grapes [ 15 , 34 , 35 , 37 , 38 ], leading to commercial formulations. Our results showed that in MD plots “trap shutdown” occurred, as male captures in pheromone traps were reduced by 97% to 100% in both fruit crops one to two months after the applications in two seasons.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Previously, studies showing the usefulness of this technique as a control tool for a mealybug species have been carried out only for Pl. ficus in grapes [ 15 , 34 , 35 , 37 , 38 ], leading to commercial formulations. Our results showed that in MD plots “trap shutdown” occurred, as male captures in pheromone traps were reduced by 97% to 100% in both fruit crops one to two months after the applications in two seasons.…”
Section: Discussionmentioning
confidence: 99%
“…The pheromone doses used in this study (6.32 and 9.45 g/ha of the stereoisomeric pheromone mixture) were much lower than those used in studies with Pl. ficus , which found effects with 62.5 and 93.8 g/ha [ 35 ]; 93 g/ha [ 36 ]; 54 to 90 g/ha [ 38 ] and 20.0 to 61.7 g/ha [ 15 ]. When lower doses were tested, such as 4.15 and 8.3 g/ha, male trap captures were similar in the MD and control treatment [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations